Effects of environmentally relevant concentrations of the antidepressant sertraline on the performance and behavior of larval amphibians - Barsoumian, Hagop Armenio (2022)
Environmental contamination by pharmaceuticals is receiving an important attention by the scientific community in the last several years. Inadequate disposal, insufficient basic sanitation and technical limitations on sewage treatment results in the detection of several compounds in surface waters around the planet. Antidepressants, particularly Selective Serotonin Recapture Inhibitors, are among them. I conducted two experiments manipulating sertraline, a Selective Serotonin Recapture Inhibitor that is the second most consumed antidepressant in Brazil. The first experiment aimed at evaluating whether environmentally relevant concentrations of sertraline influence the performance of tadpoles of Rhinella icterica as measured by survival, mass gain, development, and time to metamorphosis. No effects were observed on measured response variables. The second experiment aimed at evaluating whether environmental relevant concentrations of sertraline influence the interaction between predators and their prey. My model system comprised tadpoles of the treefrog Scinax fuscovarius as consumers, and larvae of the dragonfly Erythrodiplax sp as predators. As response variables we quantified, in the prey, parameters known to regulate predation risk such as activity level, food consumption, spatial avoidance, refuge seeking, and, swimming kinematics. No main effects of sertraline on behavioral response variables were detected; a significant sertraline-by-predator presence interaction term on activity levels was observed. By contrast, sertraline affected several swimming kinematic variables including time swimming, total displacement and number of stimuli required to induce swimming. Together, these results suggest that environmentally relevant concentrations of sertraline may provoke a reduction in the fitness of amphibian larvae.